2017
DOI: 10.1007/978-3-319-46709-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Management of Rangeland Systems

Abstract: Adaptive management is an approach to natural resource management that uses structured learning to reduce uncertainties for the improvement of management over time. The origins of adaptive management are linked to ideas of resilience theory and complex systems. Rangeland management is particularly well suited for the application of adaptive management, having sufficient controllability and reducible uncertainties. Adaptive management applies the tools of structured decision making and requires monitoring, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The high number of invader species may risk for rangelands, forage quantity and quality and livestock production, quality and health (Allen et al, 2017;Casler and Undersander, 2019;Uzun and Ocak, 2019). In general, the species richness and diversity in the rangelands decrease depending on the grazing pressure and human activities (Erkovan et al, 2016;Abdelaal et al, 2019;Uzun and Ocak, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high number of invader species may risk for rangelands, forage quantity and quality and livestock production, quality and health (Allen et al, 2017;Casler and Undersander, 2019;Uzun and Ocak, 2019). In general, the species richness and diversity in the rangelands decrease depending on the grazing pressure and human activities (Erkovan et al, 2016;Abdelaal et al, 2019;Uzun and Ocak, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The result of invader species in the studied rangeland may be related to the fact that overgrazing can increase invasive plant establishment and proliferation. Moreover, the effects of invader species on soil N and P dynamics (Eviner et al, 2012) can greatly alter plant species composition, particularly suppressing desirable native species (Allen et al, 2017). These may explain why the invasive species were relatively high and 5 species were not exclusive for the studied rangeland habitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujitani et al (2017) found that active participation in adaptive management (of fish stocking) increased stakeholders’ knowledge and capacity for management of their fisheries resources. In a project for Great Plains grassland restoration via controlled burning (Twidwell et al 2013b), maintaining involvement of landowners’ groups has been a primary goal of monitoring and evaluating effectiveness of management actions (Allen et al 2017). It is of course important to recognize that such meaningful stakeholder engagement involves increased costs to stakeholders in terms of the commitment of time and effort to attend meetings, develop knowledge, or represent a stakeholder group (Beckley et al 2005).…”
Section: Institutional Learningmentioning
confidence: 99%
“…Overall, the EWI metrics we review and, more broadly, the early warning/spatial regime paradigm represent quantitative, more objective decision-making tools for rangeland management in the face of ecological uncertainty (Lindenmayer and Likens, 2009;Allen et al, 2017). Traditional inventory and monitoring efforts are not designed with the spatial specificity needed to provide indicators of sudden change in many rangeland systems; however, statistical theory is advancing to be able to better incorporate broad-scale monitoring and inventory data for purposes of early warning and regime shift detection.…”
Section: Example 3: Advances In Rangeland Monitoring and Applicationmentioning
confidence: 99%